IN VITRO PHARMACOLOGICAL ACTIVITY TEST OF TELANG FLOWER KOMBUCHA AS ANTIBACTERIAL Vibrio Cholerae AND Shigella dysenteriae THROUGH FERMENTATION BIOTECHNOLOGY METHOD - Somantri, Ucu Wandi; Fadillah, M Fariz; Rezaldi, Firman; Pruschia, Isti Dwi; Margarisa, Dwiyarina; Maharani, Maharani (Biotik, 2023)
Diarrhea that occurs in the digestive tract is a big problem for human intestinal health. This can be caused by the activity of pathogenic bacteria in the form of Vibrio cholera and Shigella dysinteriae. In this study, kombucha has been shown to have pharmacological activity in vitro in inhibiting the growth of Vibrio cholera and Shigella dysinteriae bacteria at all sugar concentrations. The purpose of this study was to determine the in vitro pharmacological activity of the butterfly pea flower kombucha in inhibiting the growth of the two test bacteria consisting of a sugar concentration of 20%, 30% and 40%. The method for testing the inhibition of both bacterial growth tests is disc diffusion. One way ANOVA and post hoc analysis are one of the quantitative test methods used in this study of the average diameter of the inhibition zone of teal flower kombucha from various sugar concentrations. The results of this study have proven based on a one-way ANOVA with each P value> 0.05 and then continued through post hoc analysis concluded that the telang flower kombucha at a concentration of 40% is the best treatment in inhibiting the growth of both test bacteria where the concentration is significantly different from sugar concentration 20% and 30%.